Single walled carbon nanotubes on MHD unsteady flow over a porous wedge with thermal radiation with variable stream conditions - R. Kandasamy; I. Muhaimin; Radiah Mohammad (Alexandria Engineering Journal, 2016)
The objective of the present work was to investigate theoretically the effect of single walled carbon nanotubes (SWCNTs) in the presence of water and seawater with variable stream condition due to solar radiation energy. The conclusion is drawn that the flow motion and the temperature field for SWCNTs in the presence of base fluid are significantly influenced by magnetic field, convective radiation and thermal stratification. Thermal boundary layer of SWCNTs-water is compared to that of Cu-water, absorbs the incident solar radiation and transits it to the working fluid by convection.